Experiences in the Decision-Making Regarding the Place of Care of the Elderly: A Systematic Review - Gema Serrano-Gemes; Rafael Serrano-del-Rosal; Manuel Rich-Ruiz (Behavioral Sciences, 2021)
The objective of this review was to understand how participants experience the decision-making process regarding the place of care for the elderly. Therefore, we conducted a systematic review of qualitative studies. The articles were included if they were original studies with qualitative/mixed methodology, written in English/Spanish, and that approached the decision-making process regarding the place of care for the elderly, already experienced by the participants. Forty-four articles were included, identifying experiences, both negative and positive. Negative experiences have been the most frequently reported experiences by all population groups; fear was the most relevant experience for the elderly, whereas concern was the most relevant for family members and professionals. This review has not only found a great variability of experiences, but also, it has deepened the differences between groups and the situations motivating/generating these experiences. This review highlights a wide range of experiences of those directly involved in the entire decision-making process on the place of care for the elderly. In future research it would be interesting to carry out qualitative primary studies conducted with professionals and other relevant people involved in this decision-making process, in order to know first-hand how they experience this process.